On the affinities of Zuluscaphites van Hoepen 1955 (Cretaceous Ammonoidea) from the Albian of Zululand, South Africa - Kennedy, W; Klinger, H (1993)
Zuluscaphites van Hoepen 1955, an enigmatic ammonite originally described from the Middle or Upper Albian of Zululand, South Africa, is shown to be a member of the acanthoceratacean family Lyelliceratidae, subfamily Stoliczkaiinae; it is not a heteromorph as originally proposed. Huescarites Latil 1991 is a junior synonym of Zuluscaphites as are the type species of the two genera, Z. orycteropusi and H. companyi. © 1993 E. Schweizerbart'sche Verlagsbuchhandlung.